Design Review of Leuwikeris DAM Acces Road Pakage 4 - Reki Arbianto; Gunarso Gunarso (UNISSULA Semarang, 2022)
Abstract: The construction of the Leuwikeris Dam requires materials to be used for stockpiling. Therefore, it is necessary to access the road from the quarry in question to the location of the dam. This access road is located in Cibodas Village RT 32 / RW 15 Ciharalang Village, Cijeungjing District, Ciamis Regency, West Java. The construction of access roads needs to build bridges connecting the valleys which requires making embankments to reach the elevation of the road plan. The embankment is made up to ± 15 m using embankment material around the site. This design review was carried out because a landslide occurred on one of the embankment slopes which did not rule out the possibility that it could occur on the opposite slope. This design review uses the help of the SLOPE/W program to determine the level of slope safety and alternative slope reinforcement designs. It should be noted that the data used are secondary data obtained from related parties. Some things that can be concluded from the design review are as follows: 1) The landslide occurred due to the failure of the existing gabion foundation to withstand the load of the slope. 2) Repair the gabion foundation by enlarging and deepening the dimensions (attached image), so that it can cut the landslide area. The dimensions of the large foundation are expected to provide sufficient counter weight. 3) The landslide material must be cleaned and start compaction per layer from the beginning. Ensure that the backfill is of maximum density. 4) Improved gabion design so as to obtain sufficient volume weight of at least 1.5 t/m3. The installation of bamboo chimneys is still being carried out as additional reinforcement. Keywords: Safety factor; Gabion; Road; Embankment; Slopes stability; Slope-W.